COLOMBIAN DESPLAZADOS: REFLECTIONS OF THE STATE’S INOPERABILITY TO PROTECT THE SOCIAL RIGHT TO HOUSING - Piccolo, Thuany Klososki; Masson, Daiane Garcia; Santos, Cristiane Brum dos (Unoesc International Legal Seminar, 2017)
INTRODUCTION In terms of mobility rights’ violation, the attention of international organizations and the academic researches often turns to immigration. This is because the severe humanitarian crisis installed by the complex dynamics of migration experienced by European countries – as host countries - and countries like Syria – from where migrants flee. Despite this significant problem, another type of displacement must become part of the agenda for discussion and the scope of protection and performance of States and international human rights organizations. The social and economic vulnerability of millions of internally displaced persons (IDPs) around the world that live like hostages in their own country, forced to leave their homes and even their cities by the actions of armed groups, reveals itself as subject little known considering that studies in national and foreign doctrine are rare about it. In this research, the vague international protection becomes relevant factor due to the IDPs’ categorization as “refugee like situation” and the inertia of the States in the enforcement of minimum social rights to these people, particularly regarding the protection of social right to housing. Unable to confront and put an end to the armed conflict, the States fail for being omitted in human rights’ violation and for the absence of public policies to IDPs, subjecting them to severe social and economic vulnerability. The problem’s extension can be explained by the displacements of people observed in Colombia, especially from the 70s, with the emergence of Colombian militias that hide on the countryside. Since then, Colombia has been leading the ranking of IDPs for more than six decades with about six million desplazados until being overtaken by Syria in 2011. The extreme vulnerability of Colombians desplazados subjects them to extreme poverty and impedes the benefit of the adequate right to housing, guaranteed at the constitutional level. In terms of fundamental rights, it can be said that there is a total violation scenario of any moral value of human beings and because of it, this study aims to contribute to the reflection and to the socio-political practice for the non-violation of IDPs fundamental rights, addressing the specific and multifaceted problem of the Colombian context, especially in the realization of the social right to housing. METHODOLOGY The research follows the deductive method and corresponds to the bibliographic type, in which books, scientific articles and international documents, such as the United Nations reports and international treaties will be reviewed. The theme approach requires an understanding of the basic aspects of fundamental and social rights, focusing on the right to housing, the social, political and historical context of the armed conflict and its own internal displacement, the role of international humanitarian law, besides documents related to the theme and the most important principle that rules fundamental rights and guarantees: the human dignity. DISCUSSION According to recent data from the Norwegian Refugee Council (2015, p. 7), by the end of 2014 the number of IDPs increased to about thirty-eight million in more than forty countries of the African, American, European and Asian continent. The report demonstrates that Syria, Colombia, Iraq, Sudan and the Democratic Republic of Congo (DRC) have the higher rates of displacement, from seven to two million people, in descending order. Oliveira (2004, p. 75) points out that there are various definitions of IDPs however these are not fully accepted by the (few) researchers due to the breadth of the term, which allows the inclusion of other groups than those displaced, and also because there is no difference between the treatment of displacement caused by violence or by natural causes. The most widely used definition, therefore, is provided by the Guiding Principles on Internal Displacement (1998) and proposed by the Special Representative of the Secretary-General of the United Nations for Internally Displaced Persons: [...] IDPs are persons or groups of persons forced or obliged to flee or to leave their homes or places of habitual residence, in particular as a result of, or in order to avoid the effects of armed conflict, situations of generalized violence, human rights violations or human or natural disasters, and who have not crossed an internationally recognized border of a state. In this sense, Oliveira (2004, p. 75) teaches that the main feature of IDPs consists in the fact that they remain within the borders of their country of origin, although they leave their homes. So, because of it, these individuals do not qualify neither as refugees nor as migrants, therefore it is required a specific legal category in international law. Unlike Syria, that faces a declared and major civil war, Espinosa (2009, p. 1) affirms that Colombia is the scene of migratory crisis of IDPs since the 70s, especially due to the violent actions of guerrilla movements, like the Revolutionary Armed Forces of Colombia (FARC). Colombia, which led the ranking of internal displacement for more than six decades, accounted about six million of IDPs by the end of 2014, according to the Norwegian Refugee Council (2015, p. 14). Even being an extremely delicate issue, Viana (2009, p. 145) explains that the Colombian government only initiated measures to tackle it in the late 1990s with Law No. 387/1997, transferring to the State the responsibility on policy formulation and adoption of actions to support the population of desplazados. The first article of the law calls as desplazado every person forced - through violence - to leave his residence or usual economic activity and migrate within the national territory as consequence of internal armed conflict, geostrategic territories dispute, areas to practice extensive farming and commercial agriculture, among other reasons. In terms of national law, which appears to be a serious problem of Latin American constitutionalism, the constitutions establish extensive list of fundamental rights that States fail to ensure. That is because social rights depend on state actions to be implemented and their effectiveness is directly related not only in the social area, but also in the legal, economic, and political fields. At that point, it is worth mentioning the lesson from Alexy (2015, p. 446), in his renowned work Theory of Fundamental Rights, for whom "[...] fundamental rights are positions that are so important that the decision on guarantee them or not guarantee them not It can simply be left to the simple parliamentary majority". The right to housing is established in the Colombian Constitution of 1991, specifically in Article 51, which guarantees all nationals the right to a "dignified housing", promoted by the State through public policies aimed at ensuring the right[1]. As Sarlet (2015, p. 343) asserts that the right to housing can not be confused with the right to property or the right to property and are inextricably linked to the human dignity and the minimum subsistence of the human person. In the specific case of displaced people, there is interference in the right’s dual dimension, negative and positive, considering that the state fails in both the protection and the promotion of housing. Canuto (2010, p. 166-167) points out that social rights consist in means by which the human dignity is reached and, therefore, the State must constantly look for ways to make them more accessible to the entire population, especially for those who need more help. However, it is not enough to have those rights guaranteed in a minor way, but in the best possible quality that the State is able to provide. Theodoulou (1995, p. 3) explains that public policy is a complex concept that can refer to an action or omission of government designed to serve a politically defined purpose usually involving social problems. According to the same author, to outline public policy is necessary to understand the interaction of many formal and informal actors involved in the political context. In this sense, Canuto (2010, p. 187) adds that the evaluation and analysis of the progress of public policies is a way to avoid that social programs be forgotten and that public resources have proper destination. For this author, public policies consist in instruments of social justice that enable the population, especially an excluded and often overlooked part, to have the benefit of their fundamental rights. According to Oliveira (2004, p. 75), the armed conflict that has been ruined Colombia for years is considered one of the major causes of forced displacement in the country, causing disastrous consequences especially for the rural population, that suffers physical and psychological violence. In order to avoid more damages, many families choose to leave their homes, towns and cities searching for a place to live with a minimum of peace, but the reality faced by them consists in deep abandonment and misery due to the absence of an efficient care system by the Colombian government. Ultimately, Celis (2009) argues that state and society in cooperation have an ethical duty to seek social solutions to the problem of desplazados, which corresponds to one of the most vulnerable sectors of the Colombian population. This will only be possible when public policies applied to these people’s needs, as appropriate instrument to achieve the positive rights by the state, especially the right to housing. CONCLUSIONS All around the world, millions of people face war and its consequences in their lives. In Colombia, a lasting internal battle rebounds in the protection of human rights, especially in the right to housing, considering that lots of people leave their homes trying to save their lives in pursuit of dignified conditions of living. However, a relevant percentage does not reach the dream of peace and initiates a new way of life without minimal conditions of survive within the borders of their own country. They are known as internally displaced persons (IDPs) or specifically in Colombia, as “desplazados”, since Colombia led the ranking of internal displacement for decades and its judiciary system has contributed to protect these people. This problem deserves more attention from international authorities as well as the States that have populations of IDPs, taking into account that the situation itself represents a several human rights violation. In Colombia, it was identified a few initiatives to solve the problem, but apparently it demands more adequate public policies to protect the IDPs’ right to housing and human dignity. In conclusion, this essay proposes the discussion towards the dimension of the internal displacement problem in Colombia and the consequent human rights violation from it. Besides, this research identifies the State’s necessity to formulate consistent public policies to promote the effectiveness of human dignity, social right, especially the right to housing.